Level Pemahaman Konsep Fluida Mahasiswa Calon Guru Fisika dalam Project Based Laboratory (PJB-Lab) - Firmansyah, Juli; Suhandi, Andi; Setiawan, Agus; Permanasari, Anna (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2021)
Understanding Physics Concepts is a concern for every learning process and physics practicum. The development of various physics practicum concepts in the Inquiry Lab or Project Based Lab models contributes to the Students' Concept Understanding Level. This study was conducted to determine the level of conceptual understanding of students on the concept of fluid through project-based laboratory. The method used is pre-experimental with one group pretest and posttest design. The subjects of this study were 22 prospective physics teacher students at one of the universities in Banda Aceh City. The test instrument used is a level test of concept understanding in the form of a stratified description consisting of the ability to explain the concept (P), the ability to determine the laws of physics (Q), ability to provide additional case examples of related laws (R) and define those laws (S). The results showed that students achieved an understanding of fluid concepts at the level of complete understanding (CU) after participating in a project-based laboratory. Therefore, it can be concluded that the level of understanding of physics concepts effectively increases to achieve complete understanding through project-based laboratory.